2016
DOI: 10.1080/19336896.2016.1228506
|View full text |Cite
|
Sign up to set email alerts
|

On the evolutionary trajectories of signal-transducing amyloids in fungi and beyond

Abstract: ABSTRACT. In the last decade, multiple reports have established that amyloids can bear important functional roles in a variety of biological processes and in distant taxonomic clades. In filamentous fungi, amyloids are involved in a signal transducing mechanism in which a group of NOD-like receptors (NLRs) controls downstream effector proteins to induce a programmed cell death reaction. A structurally characterized example of fungal signal-transducing amyloid is the prion-forming domain (PFD) of the HET-S toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The widespread and diversity of amyloid prion domains underscores the evolutionary success of this class of signaling modules in fungi. Furthermore, we have uncovered a large variety of signaling amyloids with prion properties operating in analogous NLR-dependent signaling cascades ( Daskalov et al, 2015a ; Daskalov, 2016 ; Loquet and Saupe, 2017 ). In particular, the fungal PP motif ( Daskalov et al, 2016 ) shows sequence similarity to the RIP1/RIP3 necrosome in humans.…”
Section: Functional Prions Emerge As Trans -Kingdom Entitiesmentioning
confidence: 99%
“…The widespread and diversity of amyloid prion domains underscores the evolutionary success of this class of signaling modules in fungi. Furthermore, we have uncovered a large variety of signaling amyloids with prion properties operating in analogous NLR-dependent signaling cascades ( Daskalov et al, 2015a ; Daskalov, 2016 ; Loquet and Saupe, 2017 ). In particular, the fungal PP motif ( Daskalov et al, 2016 ) shows sequence similarity to the RIP1/RIP3 necrosome in humans.…”
Section: Functional Prions Emerge As Trans -Kingdom Entitiesmentioning
confidence: 99%
“…To date, the immunoprecipitation method revealed that RIP1/RIP3 can compose a heteroamyloid [ 149 ], although the structural and functional relationships require further clarification. It is also worth noting that the RHIM motifs of RIP proteins are homologous to the prion domain of Het-s, a prion protein of the fungus Podospora anserina , that is also involved in the programmed mycelium destruction process, controlling the cytoplasmic incompatibility, a biologically advantageous process in fungi [ 154 , 155 ]. Proteins with similar domains and roles are also found in other fungi [ 156 ].…”
Section: Functional Amyloids In Mammalsmentioning
confidence: 99%
“…This is reminiscent of the interaction between RPW8/HR proteins and the NLR protein RPP7. Adjacent HeLo-/HELL-domain encoding genes and NLR genes are found in many fungal genomes [82][83][84][85]. In addition, the mammalian NLR protein NLRP3 and its adaptor protein ASC interact in a very similar manner as HET-S and NWD2 do [86].…”
Section: Similarity Of Rpw8/hr To Fungal and Mammalian Immune Proteinsmentioning
confidence: 99%